Return to Sport After Primary Anterior Cruciate Ligament (ACL) Reconstruction: A Survey of The American Orthopaedic Society for Sports Medicine - Xu, Shin; Cheema, Sana; Tarakemeh, Armin; Randall, Jeffrey; Bechtold, Megan; Mullen, Scott; Schroeppel, Paul; Mulcahey, Mary; Vopat, Bryan (Kansas Journal of Medicine, 2023)
Introduction. Anterior cruciate ligament (ACL) tears are a common sports injury, and typically require a prolonged post operative rehabilitation. The purpose of this study was to survey members of the American Orthopaedic Society for Sports Medicine (AOSSM) to determine their return to sport (RTS) criteria after primary ACL reconstruction (ACLR).Methods. A 23 question, anonymous survey hosted through Google Docs was distributed electronically to AOSSM members. This survey included questions regarding the timing, as well as any functional tests or other metrics used to determine when an athlete is ready to RTS.Results. 863 surgeons responded over four months. The most popular graft choice was bone patellar tendon bone autograft (63%). For non-pivoting sports, 43% of respondents allowed RTS at 5 - 6 months, while 31% allowed RTS at 7 - 8 months. For pivoting sports, 34% of respondents allowed RTS at 7 - 8 months, while 36% allowed RTS at 9 - 10 months. The most common criteria for return to non-pivoting sports include full knee motion (89%) and time after ACLR (76%). The most common criteria for return to pivoting sports include full knee motion (87%) and passing a hop test (80%). Only 21% of respondents assessed for psychological readiness to RTS.Conclusions. RTS occurred sooner in non-pivoting than pivoting sports, with similar RTS criteria in both groups. Most respondents do not assess for psychological readiness to RTS.